PENGARUH MOTIVASI DAN INSENTIF TERHADAP PENILAIAN PRESTASI KERJA DOSEN TETAP DI UNIVERSITAS BUNDA MULIA - Yustinus Yuniarto (Universitas Bunda Mulia, 2017)
This study will show the effect of incentives on job performance of tenured faculty at the Bunda Mulia University where the effect is not too large, while the motivation for job performance of tenured faculty at the Bunda Mulia University has considerable influence. Keywords : Incentives, Motivation, Work Achievement